Evaluasi Kesuburan Tanah Sawah pada Sentra Pertanaman Padi Sawah di Kecamatan Wawonii Utara - Febriansyah, Muhammad Fahrul; Suleman, Darwis; Alam, Syamsu; Pasolan, Yulius B.; Leomo, Sitti; Rustam, La Ode (Agritechpedia, 2024)
Soil fertility is one of the main factors affecting agricultural land productivity. Evaluation of soil fertility in rice fields needs to be carried out to identify nutrient status and soil fertility, and to determine site-specific fertilization recommendations. This study aims to evaluate soil fertility status and determine fertilization recommendations in rice fields in Tumburano Village, North Wawonii District. This study was conducted from July to October 2023 using a random sampling survey method based on differences in slope positions, namely upper, middle and lower rice fields. Soil sampling was carried out at each slope position with 3 replications. The results showed that soil pH varied between 7.14-7.55 (neutral), soil organic C ranged from 4.04-6.29% (very high), and Total N ranged from 0.41-0.61% (very high). While available P ranged from 10.89-12.56 ppm (moderate), available K varied between 0.34-0.35 cmol (+) kg⁻¹ (low). The soil CEC varies between 24.46-27.21 me 100 g⁻¹ (medium-high) and BS ranges between 71.84-77.47% (high). Based on the results of the assessment of soil chemical properties, it can be concluded that the level of soil fertility in the study area is in the low to medium category. The results of this study recommend fertilization: 250 kg ha-1 urea, 75 kg ha-1 SP-36, and 100 kg ha-1 KCl (if using single fertilizer), and a dose of 300 kg ha-1 plus 150 kg ha-1 urea, if compound fertilizer. It is also recommended to use 5 t ha-1 of straw to reduce synthetic fertilizers